Peran Varietas Tahan dalam Menurunkan Populasi Wereng Coklat Biotipe 4 pada Tanaman Padi - E., Baehaki S.; K., Arifin; Munawar, D. (Pusat Penelitian dan Pengembangan Tanaman Pangan, 2011)
Research was carried out in a screen house at Indonesian Center for Rice Research and in the rice field at Pati, Central Java, during the Wet Season 2009. Design of each experiment was factorial with three replications. The first factor consisted of four varieties, namely IR74, Ciherang, Hipa 4, and Muncul. The second factor consisted of three insecticides, namely imidackloprid, BPMC, and deltamethrin. Results of the screen house trial showed that varieties IR74 and Ciherang were able to reduce nymph population of brown planthopper (BPH) biotype 4 generation 1 (G1) from Pati, Central Java, by 52.9% and 19.1%, respectively. Variety IR74 reduced nymph population of BPH biotype 4 generation 2 (G2) by 39.8%. The Insecticides Effectiveness (IE) values of imidakloprid, BPMC, and deltamethrin treatments at dosages 0.5 kg/ha; 1.5 l/ha, dan 0.25 l/ha, respectively, against BPH Biotype 4 Generation 1 (G1) and Generation 2 (G2) were less than 50%. Insecticides imidacloprid, BPMC, and deltamethrin each was not effective against the BPH. On the other hand, IE of imidacloprid, BPMC, and deltamethrin at the recommended dosages to BPH biotype 1 G1 in he screenhouse were 99.8%; 50.6% and 24.7%, respectively. Results of the field trial in Pati showed that varieties IR74, Ciherang, Hipa 4, and Muncul prior to 65 days after transplanting (DAT) did not reduce the BPH populations, but at 75 DAT, varieties IR74 and Ciherang reduced the BPH populations up to 52.3% and 66.1%, respectively. Decrease in the BPH population by imidacloprid ranged from 20.1-52.4% and by BPMC from 9.2-26.4%. Yield of IR74 which resistant variety to BPH Biotype 3 was significantly higher than that of Ciherang with a yield different of 3263 kg/ha.